METODE PELAKSANAAN PEKERJAAN PIERHEAD PADA PROYEK PEMBANGUNAN JEMBATAN CIKERUH DI JALAN RAYA CIBOLERANG KECAMATAN JATIWANGI KABUPATEN MAJALENGKA - Assa Fazri Maulida, Caca; Lumban toruan, Ernisari (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
ABSTRAK One of the important structures in the maritime industry, the pierhead construction used for various functions such as loading and unloading ships, stackinggoods, and other logistics activities. Hence, the construction of the pierhead requires careful planning and execution to ensure that the structure is strong, safe, and complies with safety standards and regulations applicable. The aim of carrying out this practical work is to know what is the process and method for implementing pierhead work on the project construction of the Cikeruh bridge on the Ciborelang highway, Jatiwangi District Majalengka Regency, know what tools and materials are used in carrying out pierhead work and how to care for the concrete. In the method of carrying out pierhead work there are eight stages work includes Preparatory Work, ringlock installation, Installation of working floors, concrete work, installation of formwork, pierhead casting, formwork dismantling and concrete maintenance. As for the tools used in carrying out the work Pierheads include: excavators, dump trucks, truck mixers, concrete pumps, pipes tremi, concrete vibrator, air compressor, wood cutting tool, crane, generator generator, hand tools, hand saws, wire cutters and electric drills. Meanwhile, the materials used in carrying out pierhead work namely using FC'40 concrete, reinforcing steel, 3x3 angle cast stop, ringlock, concrete decking, plywood coated with 1 side polyfilm (12 mm and 9 mm thick), profile steel or holow and wood (size 5/7 and 4/6), scaffolding, formwork oil andtie road.